MRI-determined psoas muscle fat infiltration correlates with severity of weight loss during cancer cachexia - Patzelt, Lisa; Junker, Daniela; Syväri, Jan; Burian, Egon; Wu, Mingming; Prokopchuk, Olga; Nitsche, Ulrich; Makowski, Marcus R.; Braren, Rickmer F.; Herzig, Stephan; Diaz, Mauricio Berriel; Karampinos, Dimitrios C. (Cancers, 2021)
Purpose: To evaluate the suitability of psoas and erector spinae muscle proton density fat fraction (PDFF) and fat volume as biomarkers for monitoring cachexia severity in an oncological cohort, and to evaluate regional variances in muscle parameters over time. Methods: In this prospective study, 58 oncological patients were examined by a 3 T MRI receiving between one and five scans. Muscle volume and PDFF were measured, segmentation masks were divided into proximal, middle and distal muscle section. Results: A regional variation of fat distribution in erector spinae muscle at baseline was found (p < 0.01). During follow-ups significant relative change of muscle parameters was observed. Relative maximum change of erector spinae muscle showed a significant regional variation. Correlation testing with age as a covariate revealed significant correlations for baseline psoas fat volume (r = −0.55, p < 0.01) and baseline psoas PDFF (r = −0.52, p = 0.02) with maximum BMI change during the course of the disease. Conclusion: In erector spinae muscles, a regional variation of fat distribution at baseline and relative maximum change of muscle parameters was observed. Our results indicate that psoas muscle PDFF and fat volume could serve as MRI-determined biomarkers for early risk stratification and disease monitoring regarding progression and severity of weight loss in cancer cachexia.
Gesehen am 21.10.2021